Penal systems a comparative approach - Cavadino, Michael, 1953-; Dignan, James; Cavadino, Michael, 1953-; Sage eBooks (London : SAGE, 2006)
Using analysis of 12 different countries, Michael Cavadino and James Dignan offer an international and integrated approach to comparative penology.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Corrections; Imprisonment; Criminal justice, Administration of; Punishment; Electronic books